About The Works Of Abu-L-Mu'in AnNasafi (Eurasian Journal of Learning and Academic Teaching, 2026)
The article examines the works of Abu-l-Mu'in al-Nasafi, their historical and scientific significance. The article analyzes the pen of Abu-l-Mu'in al-Nasafi and his scientific legacy through various historical and encyclopedic sources. In the study, the topics, content, chronology and scientific features of his works are highlighted, as well as the place of his works in the scientific heritage of Central Asia and Islam is shown.